(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2020)
Resumo: o presente estudo tem como objetivo analisar a relação de parceria entre a Fundação de Arte e Cultura de Ubatuba – FUNDART e a Associação Lira Padre Anchieta de Ubatuba – ALPA face à implementação do Novo Marco Regulatório das Organizações da Sociedade Civil (MROSC): Lei nº 13.019/14. São aspectos centrais da pesquisa: a adaptação de ambas as instituições à nova legislação e os avanços no desenvolvimento cultural do município de Ubatuba, localizado no Litoral Norte do Estado de São Paulo. Nortearam a produção deste relatório técnico, além da vivência profissional da pesquisadora in loco e base na observação da documentação processual-administrativa, a legislação específica, publicações e periódicos jurídicos acerca do tema. Palavras-chave: Marco Regulatório das Organizações da Sociedade Civil. Lei 13.019. Parceria. Cultura. FUNDART. ALPA. Ubatuba. Abstract: this study aims to analyze the partnership relationship between the Ubatuba Art and Culture Foundation - FUNDART and the Lira Padre Anchieta Association of Ubatuba - ALPA regarding the implementation of the New Regulatory Framework for Civil Society Organizations (MROSC): Law 13.019/14. Central aspects of the research are: the adaptation of both institutions to the new legislation and the advances in the cultural development of the city of Ubatuba, located in the North Coast of São Paulo State. Guided the production of this technical report the professional experience of the researcher on site and the observation of procedural and administrative documentation, specific legislation, publications and legal journals on the subject. Keywords: Regulatory Framework of Civil Society Organizations. Law 13.019. Partnership. Culture. FUNDART. ALPA Ubatuba.